1991
DOI: 10.1002/prot.340110305
|View full text |Cite
|
Sign up to set email alerts
|

Collective motions in proteins: A covariance analysis of atomic fluctuations in molecular dynamics and normal mode simulations

Abstract: A method is described for identifying collective motions in proteins from molecular dynamics trajectories or normal mode simulations. The method makes use of the covariances of atomic positional fluctuations. It is illustrated by an analysis of the bovine pancreatic trypsin inhibitor. Comparison of the covariance and cross-correlation matrices shows that the relative motions have many similar features in the different simulations. Many regions of the protein, especially regions of secondary structure, move in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
783
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 883 publications
(792 citation statements)
references
References 19 publications
8
783
0
1
Order By: Relevance
“…In the second method, regions of the protein that show correlated and anticorrelated movements were examined using the covariance analysis method of Ichiye and Karplus. 45 The conformational change associated with ATP binding in biotin carboxylase is best described as a hinge motion 46 where the B-domain moves relative to the other domains of the protein. 47 Comparison of the ATP-bound and the apoenzyme suggests that the hinge in biotin carboxylase is located in random loops of the polypeptide chain that link the B-domain with the A-and C-domains.…”
Section: Resultsmentioning
confidence: 99%
“…In the second method, regions of the protein that show correlated and anticorrelated movements were examined using the covariance analysis method of Ichiye and Karplus. 45 The conformational change associated with ATP binding in biotin carboxylase is best described as a hinge motion 46 where the B-domain moves relative to the other domains of the protein. 47 Comparison of the ATP-bound and the apoenzyme suggests that the hinge in biotin carboxylase is located in random loops of the polypeptide chain that link the B-domain with the A-and C-domains.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that for simulations of native states, regions of secondary structure were found to move in a correlated matter, whereas the significant anti-correlated motions for residues close in space were predicted to be destabilizing to protein structure (24,52). As shown in Figure 6, the neighboring strands in the same -sheet move in a correlated manner, with the exception of no correlated motion between the D and A strands that are thus proven to be weakly coupled.…”
Section: Val30 F Met and Leu55 F Pro Mutations Disrupt The Side Chainmentioning
confidence: 86%
“…Secondly, covariance between atomic displacements is calculated between the different conformers, and analysing these covariance values allows identifying motions involving large numbers of atoms. Generally, a small set of collective motions, the first few principal components (PCs), capture the majority of fluctuations in biological macromolecules, and often these dominant motions have been found to be relevant for biological activities 40,41 . In a third step, the conformational changes corresponding to motions along each PC can be back calculated and visualized as a series of snapshots taken along the trajectories.…”
Section: Saxs Experimentsmentioning
confidence: 99%